Factors associated with anaemia among adolescent boys and girls 10-19 years old in Nepal - Nicole D. Ford; Ram Padarth Bichha; Kedar Raj Parajuli; Naveen Paudyal; Nira Joshi; Ralph D. Whitehead Jr; Stanley Chitekwe; Zuguo Mei; Rafael Flores‐Ayala; Debendra P. Adhikari; Sanjay Rijal; Maria Elena Jefferds (Wiley, 2022)
Abstract We used data from the 2016 Nepal National Micronutrient Status Survey to evaluate factors associated with anaemia (World Health Organization cut‐points using altitude‐ and smoking‐adjusted haemoglobin [Hb]) among nationally representative samples of adolescents 10-19 years. Hb, biomarkers of micronutrients, infection and inflammation were assessed from venous blood. Sociodemographic and household characteristics, dietary diversity, pica and recent morbidity were ascertained by interview. We explored bivariate relationships between candidate predictors and anaemia among boys (N = 967) and girls (N = 1,680). Candidate predictors with P < 0.05 in bivariate analyses were included in sex‐specific multivariable logistic regression models. Anaemia prevalence was 20.6% (95% confidence interval [CI] [17.1, 24.1]) among girls and 10.9% (95% CI [8.2, 13.6]) among boys. Among girls, living in the Mountain and Hill ecological zones relative to the Terai (adjusted odds ratio [AOR] 0.28, 95% CI [0.15, 0.52] and AOR 0.42, 95% CI [0.25, 0.73], respectively), ln ferritin (μg/L) (AOR 0.53, 95% CI [0.42, 0.68]) and ln retinol binding protein (RBP) (μmol/L) (AOR 0.08, 95% CI [0.04, 0.16]) were associated with reduced anaemia odds. Older age (age in years AOR 1.19, 95% CI [1.12, 1.27]) and Janajati ethnicity relative to the Muslim ethnicity (AOR 3.04, 95% CI [1.10, 8.36]) were associated with higher anaemia odds. Among boys, ln RBP [μmol/L] (AOR 0.25, 95% CI [0.10, 0.65]) and having consumed flesh foods (AOR 0.57, 95% CI [0.33, 0.99]) were associated with lower anaemia odds. Open defecation (AOR 2.36, 95% CI [1.15, 4.84]) and ln transferrin receptor [mg/L] (AOR 3.21, 95% CI [1.25, 8.23]) were associated with increased anaemia odds. Anaemia among adolescents might be addressed through effective public health policy and programs targeting micronutrient status, diet and sanitation.